Analysis of Factory Facility Layout Design Using the Craft Algorithm Method At Pt. Focus on Ciptamakmur Bersama, Blitar - Febri E. Susanto; Rusindayanto (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
PT. FOCUS CIPTAMAKMUR BERSAMA, Blitar, East Java. is a company engaged in the manufacturing industry manufacture Hexabent (mixed fertilizer) with Bentonite raw materials (natural rock). In the process of operation PT. FOCUS TOGETHER CIPTAMAKMUR have problems at a distance of material handling systems. In this study using CRAFT algorithm and as aligning with ARC method. This method aims to determine the function of the relationship between the stations to each other and to minimize the cost of material displacement. Cost of material displacement is defined as the flow of products, the distance and cost of transport unit. Collecting data in this study through pengkuran distance between stations, material handling costs between stations (OMH per unit distance), and the number of stations that exist in the company. From the research results obtained by the method of saving CRAFT distance from the initial layout of 2,751 meters to 1,332 meters difference of 20.93 %. And earned comparisons to the costs of moving materials from Rp. 1.684.800 to Rp. 1.332.050 or occur savings of 20.93 %.